Traditional media versus social media: challenges and opportunities - Al-Quran, Marwan Walid Mohammad (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The current research study aimed to frame the ongoing and growing debate in the academic field about the overlapping relationship between traditional media and social media outlets. Particularly, the study sought to present an in-depth and inclusive discussion about the traditional media and social media, focusing on the challenges and opportunities of each type. It is worth mentioning that the present study adopted the Semi-Systematic Review Approach through which the findings of a sample of studies that are consistent and similar to the current study’s topic have been identified, selected, assessed, synthesized and summarized in an explicit and planned manner which eventually led to allow the researcher to make inferences based on analyzing the resulting summary indicated in advance. The findings of the data analysis demonstrated that the traditional media and the social media have their pros and cons. Additionally, there are major differences between the two types, including: while traditional media generally offers a wider audience pool, social media allows for more targeted distribution; social media is immediate, while traditional can be delayed due to press times; traditional media pieces are more final, where social media is dynamic; social media offers more control over the message than traditional media; social media is a two-way conversation, and traditional is one-way, i.e., with social media, the public has the opportunity to voice their opinions. Furthermore, the findings of the study revealed that although social media has become the most convenient and prevalent communication channel with the ability to reach a broader audience, and although the rise of new media, particularly social media, has put a danger to the survival of some traditional media outlets and reduced their readership and viewership, however traditional media, which is no longer as dominant as it once was, is still a relevant source of information for society and a wide audience who are looking for the credibility and reliability of the news that is circulated on social media. Finally, the study concluded that despite the fact that traditional media and social media both have their pros and cons, however the relationship between them is still a relationship of integration, not a relationship of exclusion or cancellation. Thus, instead of being pitted against one another, traditional and social media outlets can go hand-in-hand through developing a successful integration, a complementary relationship, and a sustainable sharing processes between the traditional media and the social media outlets in a collaborative, cohesive, and in an ethical manner, as such integration would enhance their roles and services, provide added values than ever, and enable them to reach the widest amount of people at an effective frequency and deliver –in record time and without interference- an easily accessible content that is more interesting and present such content in an attractive way which responds to the targeted audience’s requests and meet their expectations.